Laparoscopic trans-cystic common bile duct stone retrieval in a patient with gallbladder agenesis. Issue 3 (26th March 2019) - Bakhit, Jacqueline; Privett, Benjamin; Houli, Nezor
Abstract: Gallbladder agenesis is a rare but well-documented anatomical variation. Pre-operative diagnosis may be difficult as patients can present with typical symptoms of biliary colic and imaging may be misleading. We report a case of choledochoscopy and common bile duct stone retrieval in a patient found to have agenesis of the gallbladder intra-operatively.